Screening potential immune signatures for early-stage basal-like/triple-negative breast cancer - Min Wu; Keyu Yuan; Shuzhen Lyu; Yanping Li (World Journal of Surgical Oncology, 2022)
Abstract Background Breast cancer (BC) is a highly heterogeneous disease. Among the BC molecular subtypes, basal-like/triple-negative BC (TNBC) is characterized by a high propensity for relatively early metastases and a lack of available endocrine and targeted therapies. Therefore, this study aimed to discover potential signatures for predicting the immune response in early-stage basal-like/triple-negative BC. Method A total of 86 cases of early-stage TNBC from the TCGA and 459 cases of normal breast tissue from GTEx were enrolled and analyzed to screen out differentially expressed genes (DEGs). Then, the prognostic effect and tumor immune cell infiltration relationship with the basal-like-specific DEGs were also evaluated. Results A total of 1556 DEGs, including 929 upregulated genes and 627 downregulated genes, were screened in early-stage basal-like BC. Two prognosis-associated DEGs, GAL and TTC36, were finally found to be basal-like BC specific. However, only GAL was significantly correlated with tumor immune-infiltrating cells, especially CD8+ T cells. The expressions of GAL and TTC36 were revalidated by using the GEO dataset. Conclusion GAL might be an immune signature for the response to immune checkpoint therapy in early basal-like/triple-negative BC.